Fermi-edge singularities in the photoluminescence and magneto-optical spectra of modulation-doped v-groove quantum wires - Maciel, A; Kim, J; Davies, H; O'Sullivan, E; Ryan, J; Schwarz, A; Kaluza, A; Hardtdegen, H; Schäpers, T; Meertens, D; Dieker, C; Lüth, H (Elsevier, 2000)
A strong Fermi-edge singularity is observed in the photoluminescence spectrum of a degenerate one-dimensional electron system in modulation doped GaAs/GaAlAs v-groove quantum wires. The singularity is pronounced due to one-dimensional subband mixing, which is further enhanced by an applied transverse magnetic field. The quantum wires are grown by MOVPE on pre-patterned, semi-insulting GaAs substrates. TEM and cross-sectional atomic force microscopy studies reveal that excellent definition of quantum wires, whose profile could be adjusted by the choice of the gas sources used for the bottom Al0.3Ga0.7As barrier layer and the thickness of the quantum well.